The Optimal Degree of Reciprocity in Tariff Reduction - Pao-Li Chang (East Asian Economic Review (EAER), 2020)
This paper characterizes the optimal reciprocal trade policy in the environment of Melitz (2003) with firm productivity heterogeneity. In particular, without making parametric assumptions on firm productivity distribution, this paper derives the optimal degree of reciprocal tariff reductions that maximize the world welfare. A reciprocal import subsidy raises the industry productivity, lowering aggregate price; a reciprocal import tariff helps correct the markup distortion, increasing nominal income. With all the conflicting effects of import tariffs on welfare considered, the optimal degree of reciprocity in multilateral tariff reduction is shown to be free trade.
Keywords: F12; F13; F15; 330; Firm Heterogeneity; Reciprocal Trade Policy; Import Tariff; Markup Distortion; Aggregate Productivity